The Impact of Company Size, Quality of Public Accounting Firm (KAP), and Financial Ratios on Audit Delay in Hotel, Restaurant and Tourism Sub-Sector Companies Listed on The Beitourism Sub-Sector Companies Listed On The BEI - Putri Amanda; Nur Aliah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyse the impact of company size, quality of the Public Accounting Firm (KAP), and financial ratios on audit delay in hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange (IDX). Audit delay is an indicator of the timeliness of financial reporting which can affect the credibility and trust of investors in the company. Independent variables in this study include company size (total assets), KAP quality (Big Four and Non-Big Four KAP classification), and financial ratios represented by profitability ratios (Return on Assets). This research uses quantitative methods with multiple linear regression approaches. Data is obtained from the annual financial statements of hotel, restaurant and tourism sub-sector companies published on the IDX during a certain period. Samples were selected using purposive sampling method with certain criteria. The results showed that Company Size has no significant effect on Audit Delay, while KAP Quality and Profitability. Simultaneously, the three independent variables have a significant influence on Audit Delay. The coefficient of determination analysis shows the R Square value of 0.227 or 22.7%, which means that the independent variables are able to explain the variation in changes in Audit Delay by 22.7%, while the remaining 77.3% is influenced by other factors outside the research model.